If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + -4 = -4x + -10 Reorder the terms: -4 + -3x = -4x + -10 Reorder the terms: -4 + -3x = -10 + -4x Solving -4 + -3x = -10 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. -4 + -3x + 4x = -10 + -4x + 4x Combine like terms: -3x + 4x = 1x -4 + 1x = -10 + -4x + 4x Combine like terms: -4x + 4x = 0 -4 + 1x = -10 + 0 -4 + 1x = -10 Add '4' to each side of the equation. -4 + 4 + 1x = -10 + 4 Combine like terms: -4 + 4 = 0 0 + 1x = -10 + 4 1x = -10 + 4 Combine like terms: -10 + 4 = -6 1x = -6 Divide each side by '1'. x = -6 Simplifying x = -6
| 2=5(x+9)+8x | | 5x-6=-x-30 | | (4z^6-2z^3+5)(z^3+27i)=0 | | -2x+18=-4x+34 | | 27/(-9) | | -9x+22+11x+21=2 | | 5cx-d=ax+b | | 5x+5=2x+23 | | 22t^4+18t^2-11t^6=0 | | -6=-2/3y | | 3x+18=-3x-6 | | 6n+11-8n=22 | | X^3-1/X^3=14 | | 7=8(x+5)+5 | | 3.4a=7.004 | | 1=1/3x^2 | | 5(11-3x)+4(2x+1)=3 | | 7(x+4)-(3x-1)=8 | | (3x+4)=5x | | y=ctg(1-2x) | | y=ctg(1-2xz) | | 2+2+3=3 | | (12x+20)+(7x)+(20x-35)=180 | | 6=6(x+5)-2x | | (3x+7)=(5x-3) | | 14=x*26 | | 2(x+7)+6=26 | | (5x-1)=(6x-3) | | 2=5(x+9)8x | | T=p-ir | | 4a^2-147=a^2 | | (y-2)-(y+1)=(y-3)-2 |